1976
DOI: 10.1007/bf01291237
|View full text |Cite
|
Sign up to set email alerts
|

Perceived versus objective urban opportunities and the migration of Venezuelan youths

Abstract: A multivariate regression model incorporating both objective economic opportunity and objective quality-of-life measures is able to explain 6570 of the variation in young adult in-migration rates for thirty Venezuelan cities in 1971. The objective variables mean annual temperature, level of secondary education, and objective income at the destination are largely responsible for this explanation. A second model, incorporating variables which measure perceived economic opportunity and perceived quality-of-life a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Studies on recurrent urban travel include Cadwallader (1975), McKay, Olshavsky, and Sentell (1975), Lloyd and Jennings (1978), Potter (1978), Massam and Bouchard (1976), Piccolo and Louviere (1977), and Aldskogius (1977). Studies of migration behavior include Clark and Huntoon (1976), Jessen (1976), Jones (1978Jones ( , 1980, Jones and Zannaras (1976), Lieber (1978Lieber ( ,1979, Lloyd (1976), and White (1974White ( , 1977White ( , and 1981. The distinction between "cognitive" and "affective" has been clarified in the psychological literature by the separation of the concepts of belief and attitude (Fishbein 1968;Fishbein and Ajzen 1975) and in the geographical literature by the distinction between designative and appraisive perception (Cox 1972).…”
Section: Notesmentioning
confidence: 99%
“…Studies on recurrent urban travel include Cadwallader (1975), McKay, Olshavsky, and Sentell (1975), Lloyd and Jennings (1978), Potter (1978), Massam and Bouchard (1976), Piccolo and Louviere (1977), and Aldskogius (1977). Studies of migration behavior include Clark and Huntoon (1976), Jessen (1976), Jones (1978Jones ( , 1980, Jones and Zannaras (1976), Lieber (1978Lieber ( ,1979, Lloyd (1976), and White (1974White ( , 1977White ( , and 1981. The distinction between "cognitive" and "affective" has been clarified in the psychological literature by the separation of the concepts of belief and attitude (Fishbein 1968;Fishbein and Ajzen 1975) and in the geographical literature by the distinction between designative and appraisive perception (Cox 1972).…”
Section: Notesmentioning
confidence: 99%
“…Although spatial preferences for origins and destinations have been shown to be positively associated with migration patterns in several studies [15,18,271, they have been rejected as reliable variables in others. For example, in a study of migration in Milwaukee, Clark concluded that ' the concern with perceptual mental maps of areas of the city as explanations of resi ial mobility and the parallel concern with psychological motivations for residential location choice may be misdirected .…”
Section: Origin and Destination Factorsmentioning
confidence: 99%
“…A study by White (15) indicated that the urban per capita in-migration attraction of 25 Kentucky cities was more strongly associated with respondents' residential preferences than with income, labor surplus or size variables. Jones and Zam~aras (9) found that variables measuring Venezuelan youths' perceived economic opportunity and perceived quality of life for urban areas were strongly associated with their migration behavior.…”
Section: Introductionmentioning
confidence: 98%
“…Past research examining the linkages between mental maps of residential desirability and migration can be divided into three types: 1) Studies that reveal patterns of preference for destinations from observations of mobility (1, 2, 3, 13) 2) S~udies that measure residential preferences for alternative destinations in a migration potential context (6, 16) 3) Studies that measure the statistical significance of associations between long distance migration streams and mental maps of residential desirability (9,11,14,15) While the use of mental maps in predictive studies are lacking, the third type of research indicates a promise for prediction in that mental maps have been found to be significantly associated with migration patterns. Lloyd (11) found very high multiple correlation coefficients for outmigration from Pennsylvania and South Carolina to other states with students' *Assistant Professor, Department of Geography, Kansas State University, United States of America.…”
Section: Introductionmentioning
confidence: 99%